2014
DOI: 10.1186/1476-069x-13-79
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide retailers’ knowledge and handling practices in selected towns of Tanzania

Abstract: BackgroundApproximately 300 pesticide retailers are currently registered in Tanzania. Inadequate knowledge and unsafe handling practices among retailers may contribute to human pesticide exposure and environmental contamination. This study investigated pesticide retailers’ qualifications, work experience, safety practices and the products distributed so as to identify opportunities for preventing Acute Pesticide Poisoning (APP).MethodologyIn 2005, employees of pesticide retail firms in six Tanzanian towns were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
31
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 11 publications
9
31
1
Order By: Relevance
“…The retailers prescribed informal instructions to the farmers on how to apply and at what amount agricultural pesticides are required based on their experiences. The ndings agree with a recent study by Lekei and colleagues, which found that most of the retailers of pesticides in Tanzania are not quali ed to provide professional instructions to the end-users [71]. Similarly, most of the farmers were not knowledgeable on crop pests and diseases, pesticide usage and management of agricultural pesticides, instead relying on information received from the retailers and personal work experience.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The retailers prescribed informal instructions to the farmers on how to apply and at what amount agricultural pesticides are required based on their experiences. The ndings agree with a recent study by Lekei and colleagues, which found that most of the retailers of pesticides in Tanzania are not quali ed to provide professional instructions to the end-users [71]. Similarly, most of the farmers were not knowledgeable on crop pests and diseases, pesticide usage and management of agricultural pesticides, instead relying on information received from the retailers and personal work experience.…”
Section: Discussionsupporting
confidence: 88%
“…These ndings are in line with Shao and colleagues, who reported the magnitude of counterfeit agro-inputs in Tanzania to be as high as 46.8%, that could pose a serious risk to the ecosystem [70]. In a similar study, repacking and decanting of pesticide products in un-labelled containers was done by a quarter of pesticide dealers in six study towns in Tanzania [71]. Farmers who participated in the current study reported having experienced reduced e cacy of some pesticides, hence sprayed their crops repeatedly or at a higher quantity.…”
Section: Discussionsupporting
confidence: 86%
“…There are more than 1000 active ingredients, which are marketed as pesticides [1], and developing countries use 25% of the annual global consumption [2]. In Tanzania, a total of 300 active ingredients were registered and used by 2006 [3], including endosulfan, which is restricted by the Stockholm Convention due to its environmental persistence and the documented toxic potential [4]. Furthermore, the Tanzanian pesticide import increased from 500 to 2500 tonnes between 2000 and 2003 and the Arusha region, which is the study location of the present study, is one of the heavy pesticide users in Tanzania .…”
Section: Introductionmentioning
confidence: 99%
“…(1998), describe the roles of and requirements for all relevant stakeholders in view of the management of quality of pesticides, import requirements, registration, certification, and approval, as well as requirements associated with licensing and labeling, packaging, and storage. However, despite statutory obligations being imposed on registered retailers, 32 unregistered pesticides are found across the country, especially in regions and districts bordering other countries (National Audit Office, 2018a; Lekei et al, 2014a). Illegal pesticide imports due to a lack of modern control tools at the country's borders and infrequent inspections are considered key underlying reasons, together with a significant shortage of skilled and qualified inspectors, weak implementation of sanctions to pesticide sellers and importers that do not comply with legislation, and registered pesticides not being available to key users (National Audit Office, 2018a).…”
Section: Pesticide Pollutionmentioning
confidence: 99%
“…of the risks stemming from the improper use of pesticides exposes farmers and the environment to significant risks (National Audit Office, 2018a; Lekei et al, 2014b). For example, in a case study conducted among Arumaru farmers in the Arusha region, Lekei et al (2014a) found that 79 percent of their sample reported keeping pesticides inside their homes, often in rooms used by several family members, while 5 percent used drinking water containers to mix pesticides in, and more than 40 percent applied pesticides without proper personal protection equipment. Many farmers discard leftover pesticides on their farmspouring them on the ground or burying them.…”
mentioning
confidence: 99%